Surgical Treatment of Bilateral Atrophic Mandible Fracture - Florentino, Vinícius Gabriel Barros; Abreu, Diego Feijão; Ribeiro, Ney Robson Bezerra; Silva, Leonardo de Freitas [UNESP]; Gondin, Ricardo Franklin; Mello, Manoel de Jesus Rodrigues; Aguiar, Andréa Silvia Walter de (Wolters Kluwer, 2020)
Poor proprioception, weakness, and impaired reflexes increase the incidence of facial fracture in the elderly. Mandibular fractures in these people range from 10.1% to 56%. Fragment reduction and fracture consolidation are difficult due to bone atrophy, decreased capacity for bone regeneration, and lack of anatomical landmarks to guide the alignment of the fragments. This study reports 2 patients with different conducts regarding the treatment of bilateral fractures in atrophic mandible. The first patient refers to the removal of plates of the 2.4 mm system with low profile, which failed during the mandibular function, being replaced by the 2.4 mm system with high profile. The 2nd clinical reports the use of the 2.0 mm system only to simplify the mandibular fracture, and then reconstructing that with a 2.4-mm system with high profile, using the load bearing principles. Regarding mandibular fractures, an important goal is to neutralize the muscle action aiming the bone stability. There are several methods to treat that the indication should consider the load bearing and load sharing concepts. The incorrect fixation choice in these patients can result in complications as bad union, material failure, infection, and consequent treatment failure.